Arrhythmic Risk in Biventricular Pacing Compared With Left Bundle Branch Area Pacing: Results From the I-CLAS Study - Herweg, Bengt; Sharma, Parikshit S; Cano, Óscar; Ponnusamy, Shunmuga Sundaram; Zanon, Francesco; Jastrzebski, Marek; Zou, Jiangang; Chelu, Mihail G; Vernooy, Kevin; Whinnett, Zachary I; Nair, Girish M; Molina-Lerma, Manuel; et al. (Circulation (New York, N.Y.), 2024)
BACKGROUND: Left bundle branch area pacing (LBBAP) may be associated with greater improvement in left ventricular ejection fraction and reduction in death or heart failure hospitalization compared with biventricular pacing (BVP) in patients requiring cardiac resynchronization therapy. We sought to compare the occurrence of sustained ventricular tachycardia (VT) or ventricular fibrillation (VF) and new-onset atrial fibrillation (AF) in patients undergoing BVP and LBBAP. METHODS: The I-CLAS study (International Collaborative LBBAP Study) included patients with left ventricular ejection fraction ≤35% who underwent BVP or LBBAP for cardiac resynchronization therapy between January 2018 and June 2022 at 15 centers. We performed propensity score-matched analysis of LBBAP and BVP in a 1:1 ratio. We assessed the incidence of VT/VF and new-onset AF among patients with no history of AF. Time to sustained VT/VF and time to new-onset AF was analyzed using the Cox proportional hazards survival model. RESULTS: Among 1778 patients undergoing cardiac resynchronization therapy (BVP, 981; LBBAP, 797), there were 1414 propensity score-matched patients (propensity score-matched BVP, 707; propensity score-matched LBBAP, 707). The occurrence of VT/VF was significantly lower with LBBAP compared with BVP (4.2% versus 9.3%; hazard ratio, 0.46 [95% CI, 0.29-0.74]; P<0.001). The incidence of VT storm (>3 episodes in 24 hours) was also significantly lower with LBBAP compared with BVP (0.8% versus 2.5%; P=0.013). Among 299 patients with cardiac resynchronization therapy pacemakers (BVP, 111; LBBAP, 188), VT/VF occurred in 8 patients in the BVP group versus none in the LBBAP group (7.2% versus 0%; P<0.001). In 1194 patients with no history of VT/VF or antiarrhythmic therapy (BVP, 591; LBBAP, 603), the occurrence of VT/VF was significantly lower with LBBAP than with BVP (3.2% versus 7.3%; hazard ratio, 0.46 [95% CI, 0.26-0.81]; P=0.007). Among patients with no history of AF (n=890), the occurrence of new-onset AF >30 s was significantly lower with LBBAP than with BVP (2.8% versus 6.6%; hazard ratio, 0.34 [95% CI, 0.16-0.73]; P=0.008). The incidence of AF lasting >24 hours was also significantly lower with LBBAP than with BVP (0.7% versus 2.9%; P=0.015). CONCLUSIONS: LBBAP was associated with a lower incidence of sustained VT/VF and new-onset AF compared with BVP. This difference remained significant after adjustment for differences in baseline characteristics between patients with BVP and LBBAP. Physiological resynchronization by LBBAP may be associated with lower risk of arrhythmias compared with BVP.
Keywords: Humans; Cardiac Resynchronization Therapy; výsledek terapie; srdeční resynchronizační terapie; Ventricular Function, Left; komorová tachykardie; srdeční selhání; Ventricular Fibrillation; funkce levé komory srdeční; elektrokardiografie; Heart Failure; Electrocardiography; Treatment Outcome; Tachycardia, Ventricular; tepový objem; Stroke Volume; lidé; fibrilace komor